Blockchain Technology as an Innovation in Tax Administration: A Study of its Impact on Tax Compliance - Ikhlas Alviansyah; Haryono Haryono; Rusliyawati Rusliyawati; Juanda Astarani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to analyze the influence of blockchain technology on tax compliance, with ease of digital tax administration as a mediating variable. The background of this research lies in the importance of technological innovation in building a transparent, efficient, and accountable tax administration system. The research method used is a quantitative approach with analysis techniques based on Partial Least Squares Structural Equation Modeling (PLS-SEM), utilizing data from taxpayers who possess a Taxpayer Identification Number (NPWP) and are employed at the Audit Board of Indonesia (BPK) in West Kalimantan. The results show that blockchain technology has a positive and significant influence on tax compliance, as well as a positive effect on the ease of digital tax administration. Furthermore, ease of digital tax administration is also proven to have a positive and significant effect on tax compliance. Another key finding indicates that ease of digital administration mediates the relationship between blockchain technology and tax compliance. Therefore, integrating blockchain technology into the tax system will be more effective if supported by an administrative system that is user-friendly, efficient, and digitally integrated. This study offers important implications for tax authorities in designing technology-based policies that can sustainably improve tax compliance.